Aswaja An-Nahdliyyah Module Innovation Based on Competitive Learning - Amri Amanulloh, Mochammad Ja'far; Rochmawati, Rochmawati; Rochmah, Luthfi Maulida; Muzakky, Mohamad Irvan (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to develop an Aswaja An-Nahdliyyah learning module based on Competitive Learning, integrated with the Independent Learning curriculum. The focus of this research is to improve the quality of Aswaja's teaching by emphasizing moderate and inclusive Islamic values to ward off radicalism.Method – The approach used is Asset-Based Community Development (ABCD) which involves five stages: Discovery, Dream, Design, Define, and Destiny. The development process of this module is carried out by identifying community assets, as well as involving educators in the design process. The results were evaluated through a validity test with 2 experts and effectiveness using a paired t-test using SPSS.Findings – The validation results show that this module is considered feasible by experts with an average score of 4.36. The effectiveness of the modules was tested through pre-test and post-test. The average pre-test score was 194 with a standard deviation 483, while the post-test increased to 354 with a standard deviation 382. The correlation between the pre-test and post-test of 0.671 shows a strong relationship between students' initial understanding and results after using the module. The paired t-test produced a t-value of -24.146 with p<0.001, indicating a significant difference between the pre-test and the post-test. Research Implications – These findings show the potential for the development of local curricula based on moderate values to shape a more inclusive character of students. The implications of this research are relevant in creating more efficient and competitive-based teaching methods, but limited samples and limited access to technology pose challenges in wider application.